Significant Positive Impact of Regular Exercise on Mental and Physical Health - Kalfin , Dr. Kalfin; Yuningsih, Siti Hadiaty; Prabowo, Agung (Corespub, 2024)
This article discusses the important role of regular exercise in improving mental and physical health. By reviewing a range of scientific studies and reports, it highlights the diverse benefits of physical activity, including improved cardiovascular health, muscle strength, flexibility and mental well-being. The methods used in this research included a comprehensive literature review of existing studies, providing an in-depth understanding of the positive impact of regular exercise. The results show that consistent physical activity significantly reduces the risk of chronic diseases, such as heart disease and diabetes, and reduces symptoms of mental health disorders such as depression and anxiety. In addition, exercise has been shown to improve mood, increase overall life satisfaction and improve quality of life. In conclusion, regular exercise should be promoted as an important part of a healthy lifestyle to improve individuals' overall well-being. This promotion is important to create a healthier, more resilient and happier society, by minimizing the risk of disease and strengthening mental and physical health.